A Retrospective Database Review of the Indications, Complications, and Incidence of Subsequent Spine Surgery in 12, 297 Spinal Cord Stimulator Patients. Issue 5 (22nd April 2019) - Labaran, Lawal; Jain, Nikhil; Puvanesarajah, Varun; Jain, Amit; Buchholz, Avery L.; Hassanzadeh, Hamid
Abstract : Study Design: Retrospective review. Objective: To analyze the indications, incidence of minor and major complications, and rate of subsequent spinal surgery or revision after spinal cord stimulator (SCS) placement for degenerative spine disease. Summary of Background Data: Despite the application of SCS in various chronic pain conditions, there remains a growing debate on the efficacy and necessity of SCS in degenerative spine disease. Methods: A nationally representative sample of Medicare patients who had an open (via laminectomy) SCS placement for degenerative spine disease between 2005 and 2014 were studied. Indications, complications, and the rate of subsequent spinal surgery within 90 days, one year, two years, and three years postoperatively were studied using Current Procedural Terminology (CPT) and International Classification of Diseases (ICD) codes. Results: We included 12, 297 SCS patients in our study cohort. The most common indications for SCS placement were postlaminectomy syndrome (25.2%) and chronic pain syndrome (20.2%). There was a 4.2 and 17.2% incidence of postoperative back or spine emergency department (ED) visits, and a 0.3 and 3.4% incidence of SCS electrode removal or reimplantation within 90 days and 1 year, respectively. Other reported surgical complications were wound infection (4.3%), hematoma (0.5%), and seroma (0.4%) at one year postoperatively. Within 90 days after SCS implantation, the rate of subsequent spine surgery or revision was 0.9%. This incidence was 7.1, 11.7, and 15.5% at one, two, and three years, respectively. Conclusions: In our retrospective analysis of Medicare patients, the most common indication for SCS implantation was postlaminectomy syndrome. Common postoperative complications included wound infection, and removal of SCS electrodes at one year postoperatively. About 17% patients had an ED visit for spine‐related symptoms within one year of device implantation, and 15.5% underwent subsequent spinal decompression and/or fusion within 3 years after primary SCS placement.